A multi-method approach reveals long- and short-term dietary differences in individual harbour porpoises Phocoena phocoena in the southern North Sea - Heße, Eileen; Boyi, Joy Ometere; Das, Krishna; Jung, Klaus; Lehnert, Kristina; Piette, Mathilde; Pinzone, Marianna; Schückel, Sabine; Schückel, Ulrike; Siebert, Ursula; Gilles, Anita (Marine Ecology Progress Series, 2025)
Understanding predator-prey relationships is essential for revealing the complex role of marine mammals in exerting top-down control within marine ecosystems and is crucial for developing effective conservation strategies. The harbour porpoise Phocoena phocoena is the most abundant cetacean species in the North Sea, and most studies on its diet are based on traditional hard part analysis in stomachs providing limited knowledge of its complex feeding ecology. Here, we combined stomach content analysis (SCA), metabarcoding and stable isotope analysis on the same 48 individuals, stranded between 2005 and 2021, to elucidate the diet of harbour porpoises in the southern North Sea. We aimed to increase prey species detection rates and to uncover temporal changes in the diet by comparing individual diets immediately prior to stranding with assimilated diets. By using SCA and metabarcoding complementarily, we were able to increase species detection by 49% on an individual sample level and uncovered a previously unknown prey species, hooknose Agonus cataphractus. Adult harbour porpoises primarily obtain energy from common sole Solea solea and sandeels, while juveniles rely mainly on whiting Merlangius merlangus, reflecting distinct energy sources aligned with biomass estimates. Direct method comparison revealed great temporal dietary differences in adult and juvenile porpoises. Near-shore species with a benthic carbon source contributed most to the short-term diet, whereas offshore species with a pelagic carbon source contributed most to the long-term diet. This framework can be extended to other ecosystems and predator species to elucidate the species-specific diets of animals where direct observations are not feasible.